Pengaruh Ekstrak Daun Tarap (Artocarpus odoratissimus) dalam Menghambat Perkembangan Cendawan Colletotrichum spp. Penyebab Penyakit Antraknosa Pada Tanaman Cabai - Rizani, Ridwan; Fitriyanti, Dewi; Aidawati, Noor (www.ulm.ac.id, 2025)
Chili is one of the agricultural commodities that is widely cultivated because it has many benefits for both the economy and health. However, the main obstacle that often occurs in chili plants is the presence of Plant Pest Organisms (OPT). One of them is the attack of anthracnose disease caused by fungi Colletotrichum spp. One of the natural controls that can be used is the use of plant pesticides from tarap leaves (Artocarpus odoratissimus). Tarap leaves produce a number of secondary metabolites including phenolic compounds, flavonoids, saponins, alkaloids and tannins. The purpose of this study was to determine the effect of tarap leaf extract (A. the most fragrant) in inhibiting the growth of fungi Colletotrichum spp. causes anthracnose disease in chili plants. This research was conducted from June to December 2023 at the Phytopathology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The research method used a single factor Completely Randomized Design (CRD) consisting of 5 treatments with 4 replications. Treatment T0 (Control 0%), T1 (1% tarap leaf extract), T2(3% tarap leaf extract), T3(5% tarap leaf extract) and T4(7% tarap leaf extract). The results of the study showed that giving tarap leaf extract with a concentration of T1 (1% tarap leaf extract), T2(3% tarap leaf extract), T3(5% tarap leaf extract) and T4(7% tarap leaf extract) provides colony inhibitionColletotrichumspp. highest inhibition (92.76%) at a concentration of 7% (T4) and the lowest inhibition (15.32%) at a concentration of 1% (T1).